Small town branding for tourism purposes: Working with cultural values - Tatyana Yu. Bystrova (Управление культурой)
The article specifies the territorial branding definition as an economic and socio-cultural practice. The author characterizes branding as an activity aimed at identifying the most significant characteristics of a particular site for a specific target audience, as well as distribution information about it through various communication channels. Thereafter, territorial branding is based on the ideas of the place uniqueness and identity, which are determined by natural and climatic features, culture, art, innovative and other technologies, directions of socio-economic development, living standart and other objective circumstances. Based on the history of the place and the people inhabiting it, territorial branding “reformats” the attitude of representatives of various target audiences to the place, influences the residents assessment and selfesteem, transmits information about uniqueness, performing many cultural tasks. This makes it the relevant tool for tourism projects. Based on the generalization of the genesis and existing approaches of territorial branding theorists and practitioners, the author shows its specificity in small Russian towns at the present stage and determines a number of indicators of the town state, when branding is more relevant than other social and communicative technologies. The branding integrative model presented in the text provides a more comprehensive vision of this technology. It is rational to rely on the cultural branding ideas associated with the identification and shaping of the territory values that determine its uniqueness and identity, rather than constructing a brand using images or ideas brought in from the outside in the case of tourism development in a small town. In this regard, special attention in the article is paid to the position of J. Grant, who talks about the use of cultural ideas in building a «brand molecule». Visualization of the values of tourist brands of small towns in the Sverdlovsk region is illustrated by projects of UrFU students on design support for the branding of Bilimbay and Revda, completed in 2017-2024 (Master's program «Graphic Design»).